Biçim, tarih, özne: bağlamlararası bir eleştiriye doğru - Tahan, Kağan (My University, 2016)
BİÇİM, TARİH, ÖZNE: BAĞLAMLARARASI BİR ELEŞTİRİYE DOĞRU Yirminci yüzyılın biçimci eleştiri okullarının, anlatımın anlatılan üzerindeki belirleyiciliği anlayışıyla gerçekleştirdikleri eleştirel devrim, modern edebiyat teorisinin yanı sıra yirminci yüzyılda gerçeklik ile kurulan ilişkinin kavramsal paradigmasını oluşturmuştur. Bununla birlikte Biçimciliğin biçim kavrayışı bir dizi eleştirel sorunu beraberinde getirmiştir: edebî biçimin nesnel bir kategori olarak kavranması; biçimin kapalı, bütünlüklü, organik bir yapı olarak ele alınması; edebî eserin içi ve dışı arasında keskin bir ayrım yapılması. Bu eleştirel sorunlar da bir dizi felsefî soruna yol açmıştır: yapı-tarih karşıtlığı ve kültür-birey karşıtlığı. Bu tezde, biçimin edebî metinlerle girdiğimiz ilişkiyi belirleyen temel unsur olmasından hareketle nasıl bir biçim anlayışının sözü edilen sorunların üstesinden gelerek eleştiriyi sadece politik açıdan daha etkin değil, aynı zamanda yaratıcı bir özgürlük alanı kılabileceği sorusuna cevap aranmaktadır. Bu doğrultuda, biçimci okulların eleştiri anlayışları ve Biçimcilik sonrası okulların biçime dair tartışmalara dâhil olma şekilleri sorunsallaştırılmış; ve bu soruşturmanın sonuçlarından hareketle, yeni bir biçim anlayışına dayanan yeni bir eleştiri yaklaşımı önerilmiştir. Bu tezde önerilen bağlamlararası eleştiri, biçimlerin bağlamlar arasındaki işlevsel dönüşümlerini araştırarak biçimi nesnel bir kategori olmaktan çıkaran; yapı-tarih karşıtlığına dayanmayışıyla biçimi tarihselleştiren; buna bağlı olarak, yorumsal çoğulluğa zemin hazırlayan; kültür-birey karşıtlığına dayanmayışıyla eleştirmen/ okuru fail kılan bir eleştiri yaklaşımıdır. Tarih, Özne, Bağlamlararasılık, Modernizm

FORM, HISTORY, SUBJECT: TOWARDS AN INTERCONTEXTUAL CRITICISM The critical revolution created by the formalist schools of criticism in the twentieth century with their understanding that narattion determines the narrated, constitutes the conceptual paradigm both of literary theory and of modern man’s relationship with reality. Nonetheless, the understanding of form adopted by these formalist schools caused a series of critical problems, namely the evaluation of form as an objective category; the evaluation of form as a closed, integrated and an organic structure; and the sharp distinction made between the inside and the outside of the work. These critical problems caused a series of philosophical problems, namely the dichotomy between structure and history and between culture and the individual. Based on the understanding that form is the main determinant in our relationship with literary texts, this thesis aims to provide an answer to the following question: “What are the properties of an understanding of form that can overcome the mentioned problems and render criticism not only politically more active, but also an area of creative freedom. With this aim, the formalist schools’ iv understanding of criticism and the way the post-formalist schools engaged in these discussions is problematized; and based on the results of this examination, a new approach of criticism that is built on a new understanding of form is proposed. Intercontextual criticism that has been suggested in this thesis is an approach that examines the functional transformation of forms between different contexts and thus ceases to reproduce an objective understanding of form; an approach that historicizes form, not depending on the dichotomy between structure and history; and correspondingly, that provides the grounds for interpretive multiplicity; and lastly, an approach that renders the critic/ reader an agent by ceasing to reproduce the dichotomy between culture and the individual. Form, History, Subject, Intercontextuality, Modernism
Keywords: Biçimselcilik (Edebi analiz); Edebiyat; Rus edebiyatı; Tarih ve eleştiri